Cognitive Bias and Blindness: A Global Survey of Forensic Science Examiners - Kukucka, Jeff; Kassin, Saul M.; Zapf, Patricia A.; Dror, Itiel E. (Journal of applied research in memory and cognition, 2017)
Exposure to irrelevant contextual information prompts confirmation-biased judgments of forensic science evidence (Kassin, Dror, & Kukucka, 2013). Nevertheless, some forensic examiners appear to believe that blind testing is unnecessary. To assess forensic examiners' beliefs about the scope and nature of cognitive bias, we surveyed 403 experienced examiners from 21 countries. Overall, examiners regarded their judgments as nearly infallible and showed only a limited understanding and appreciation of cognitive bias. Most examiners believed they are immune to bias or can reduce bias through mere willpower, and fewer than half supported blind testing. Furthermore, many examiners showed a bias blind spot (Pronin, Lin, & Ross, 2002), acknowledging bias in other domains but not their own, and in other examiners but not themselves. These findings underscore the necessity of procedural reforms that blind forensic examiners to potentially biasing information, as is commonplace in other branches of science. General Audience Summary Forensic science errors have been found in many cases where innocent people were wrongly convicted of crimes. Research suggests that some of these errors may be due to confirmation bias-the tendency to interpret new information in ways that confirm one's pre-existing beliefs. Some forensic labs have taken steps to protect against confirmation bias, while others have resisted doing so. To better understand forensic scientists' beliefs about bias, we surveyed over 400 professional forensic scientists from 21 countries. Although most agreed that bias is a problem in forensic science, few believed that bias affects them personally. Many also opposed procedures that are commonly used to prevent bias in other branches of science, and instead felt that willpower alone can prevent bias. We hope that our results can be used to encourage science-based reforms that will maximize the value of forensic science evidence.